Efficiency Enhancement of Thermophotovoltaic Cells With Different Design Configurations Using Existing Photon Recycling Technologies - Usman, Muhammad; Kazim, Ali H.; Shabbir, Aqsa; Abbasi, Muhammad Salman; Sarwar, Jawad (Frontiers in Energy Research, 2022)
This work deals with different design configurations using existing photon recycling technologies such as front spectral filters and back surface reflectors (BSRs) to improve the efficiency of the thermophotovoltaic (TPV) cells. On the TPV cell surface, some photons absorb, but some quantity of them is lost due to the interference on the surface. On the other hand, BSR mounted on the backside of the cell reflects all photons which were not absorbed by TPV back to the front side of the cell and the emitter, which leads to the elevated temperature of the cell and more interference on the cell surface. This work aimed to design a configuration of the TPV system model using hybrid photon recycling technologies and to investigate the efficiencies of different TPV cells with numerous factors such as emitter temperature and reflectivity of the spectral filter. The design parameters and configuration of front filters with BSRs are studied under 2500 K temperature of the emitter. It is found that an InGaAs cell with reasonable bandgap energy of 0.72 eV, is the most favorable cell material as its bandgap wavelength (1.68 μm) is closely matched to the peak wavelength (1.65 μm) of the emissions spectra. The results show that the incorporation of magnesium oxide (MgO) spectral filter along with the BSR (R = 1) and the emitter temperature of 2200 K efficiency as high as 35% can be attained. This makes MgO a viable choice in TPV cell system under concentrated solar power plant.